Prevalence of Autonomic Dysreflexia in Patients with Spinal Cord Injury above T6. (26th October 2017) - Lee, Eun Sun; Joo, Min Cheol
Abstract : Objective . To investigate the prevalence of autonomic dysreflexia (AD) using ambulatory blood pressure monitoring (ABPM) and the autonomic dysfunction following spinal cord injury (ADFSCI) questionnaire in patients with spinal cord injury (SCI) above T6. Methods . Twenty-eight patients diagnosed with SCI above T6 were enrolled. ABPM and ADFSCI were utilized to assess AD. Using ABPM, systolic blood pressure (SBP), diastolic blood pressure, and heart rate (HR) were measured at 30-minute intervals. AD was defined as SBP 20 mmHg higher than basal SBP, and the number of AD events was counted. The ADFSCI questionnaire evaluates the severity and frequency of the AD symptoms. Results . According to the ABPM, AD occurred in 26 patients and AD events occurred 5.8 ± 4.7 times. Average daytime and nighttime SBP were 119.9 ± 18.8  mmHg and 123.8 ± 21.2  mmHg, respectively, and the nighttime mean SBP appeared to be 4 mmHg higher than daytime mean SBP. These findings suggest the loss of nocturnal BP dipping in SCI patients. ADFSCI results revealed that 16 of the patients evaluated were symptomatic while 12 were asymptomatic. Conclusion . AD following SCI above T6 was highly prevalent and several patients seemed asymptomatic. These results suggest the necessity of proper diagnostic and therapeutic interventions for managing AD.